The visual amplification of goal-oriented movements counteracts acquired non-use in hemiparetic stroke patients. Issue 1 (December 2015) - Ballester, Belén; Nirme, Jens; Duarte, Esther; Cuxart, Ampar; Rodriguez, Susana; Verschure, Paul; Duff, Armin
Abstract Background Stroke-induced impairments result from both primary and secondary causes, i.e. damage to the brain and the acquired non-use of the impaired limbs. Indeed, stroke patients often under-utilize their paretic limb despite sufficient residual motor function. We hypothesize that acquired non-use can be overcome by reinforcement-based training strategies. Methods Hemiparetic stroke patients (n = 20, 11 males, 9 right-sided hemiparesis) were asked to reach targets appearing in either the real world or in a virtual environment. Sessions were divided into 3 phases: baseline, intervention and washout. During the intervention the movement of the virtual representation of the patients' paretic limb was amplified towards the target. Results We found that the probability of using the paretic limb during washout was significantly higher in comparison to baseline. Patients showed generalization of these results by displaying a more substantial workspace in real world task. These gains correlated with changes in effector selection patterns. Conclusions The amplification of the movement of the paretic limb in a virtual environment promotes the use of the paretic limb in stroke patients. Our findings indicate that reinforcement-based therapies may be an effective approach for counteracting learned non-use and may modulate motor performance in the real world.